Adipose-derived stem cells in the treatment of hepatobiliary diseases - Satilmis, B; Cicek, GS; Cicek, E; Akbulut, S; Sahin, TT; Yilmaz, S (2022)
Determination of the mesenchymal stem cells is one of the greatest and most exciting achievements that tissue engineering and regenerative medicine have achieved. Adipose-derived mesenchymal stem cells (AD-MSC) are easily isolated and cultured for a long time before losing their stem cell characteristics, which are self-renewal and pluripotency. AD-MSC are mesenchymal stem cells that have pluripotent lineage characteristics. They are easily accessible, and the fraction of stem cells in the adipose tissue lysates is highest among all other sources of mesenchymal stem cells. It is also HLA-DR negative and can be transplanted allogenically without the need for immunosuppression. These advantages have popularized its use in many fields including plastic reconstructive surgery. However, in the field of hepatology and liver transplantation, the progress is slower. AD-MSC have the potential to modulate inflammation, ameliorate ischemia-reperfusion injury, and support liver and biliary tract regeneration. These are very important for the treatment of various hepatobiliary diseases. Furthermore, the anti-inflammatory potential of these cells has paramount importance in the treatment of sepsis. We need alternative therapeutic approaches to treat end-stage liver failure. AD-MSC can provide a means of therapy to bridge to definitive therapeutic alternatives such as liver transplantation. Here we propose to review theoretic applications of AD-MSC in the treatment of hepatobiliary diseases and sepsis. C1 [Satilmis, Basri; Sahin, Tevfik Tolga; Yilmaz, Sezai] Inonu Univ, Liver Transplant Inst, Hepatol Res Lab, TR-44000 Malatya, Turkey. [Satilmis, Basri] Inonu Univ, Fac Pharm, Dept Biochem, TR-44000 Malatya, Turkey. [Cicek, Gizem Selen] Malatya Training & Res Hosp, Dept Anesthesiol & Reanimat, TR-44000 Malatya, Turkey. [Cicek, Egemen; Akbulut, Sami; Sahin, Tevfik Tolga; Yilmaz, Sezai] Inonu Univ, Liver Transplant Inst, TR-44000 Malatya, Turkey. [Sahin, Tevfik Tolga] Inonu Univ, Liver Transplant Inst, Hepatol ...